PERCEIVED QUALITY OF COUNTERFEIT PERFUME AND ORIGINAL PERFUME - Turk, Caleb Elijah; Saerang, David Paul Elia (Universitas Sam Ratulangi, 2015)
Abstract: Perfume is one type of product that often has prestigious prices tied with quality to attract consumers, which (as often is seen with high-priced products) arouses the interests of counterfeiters to copy the originals. Perfume comes in many fragrances which are offered to customers. Fragrances have their own characteristics in order to match with the various tastes, moods, and occasions they may want them for. Perfume also can reflect certain life-styles. Perfume creates different perceived values depending on the consumer. The purpose of this research is to determine the differences of consumers’ perceived quality between counterfeit and original perfume. This research uses comparison method based on data gathered from 100 respondents from the Faculty of Economics and Business, Sam Ratulangi University. By using independent sample t-test with SPSS program to analyze the data, this research found difference in consumer perception of counterfeit perfume and original perfume. As seen from the mean difference, original perfumes have more positive perception by consumers compared to counterfeit perfumes. Company management who produce original perfume should consider the market for their products in Manado, as the people here perceive original perfume to be better than counterfeit. Keywords: consumers perceived quality, counterfeit perfume, original perfume